The Effect of PHBS Health Education on the Knowledge of 4th Grade Students at SDN 35 Gresik - Mahendra, Muamar; Piesesha, Frieska; Putri, Lidia Aditama; Suhartini, Titik; Arfah, Muh.; Wibowo, Bima Ardiyanto (Indonesian Journal of Medical Sciences and Public Health, 2025)
The implementation of Clean and Healthy Living Behavior (PHBS) in schools must begin at the elementary level, considering that elementary school is a golden period for instilling clean and healthy living habits. The purpose of this study was to determine the knowledge scores of students before and after being given education on PHBS. This study used a descriptive epidemiological design. The study population consisted of all 4th grade students at SDN 35 Gresik. The sample was determined using a total sampling technique, so all 49 students were included as respondents. Data analysis was conducted descriptively and using a paired t-test to determine the effectiveness of increasing students’ knowledge before and after the intervention. The results showed that the students involved in this study consisted of 23 male and 26 female students. There was an increase in the average knowledge score from 77.55 in the pre-test to 86.12 in the post-test. This increase was also accompanied by a decrease in the standard deviation, indicating that the variation in scores among students became more uniform after the education was given. Based on the paired t-test, the p-value was less than 0.05, indicating a significant difference between pre-test and post-test scores. Thus, PHBS education proved to have a real effect on increasing the knowledge of 4th grade students at SDN 35 Gresik.